DEVELOPMENT OF QUANTUM LEARNING LEARNING MODEL THROUGH ARISAN CARDS TO INCREASE STUDENT MOTIVATION AND LEARNING OUTCOMES - Rahmawati, Fitri; Sutisna, Muhamad (UNIVERSITAS PAKUAN, 2021)
The low learning motivation and learning outcomes of students occur because there are several problems such as the attitude of students who are indifferent to the learning process, students do not pay attention when the teacher explains the material and do not do the assignments given by the teacher, the lack of interest of students in Pancasila Education subjects and Citizenship. This study aims to find a quantum learning model through arisan cards to increase student motivation and learning outcomes. The research method used Research and Development This research was conducted in three product trials. The subjects of this study were class VIII students with 36 students in the 2019-2020 school year. Data collection techniques include expert verification sheet learning models, verification of material experts, observation of learning motivation and student learning outcomes, interview sheets and documentation. The results showed; The percentage of observation results of learning motivation and learning outcomes of students in the first trial, namely motivation by 58%, pretest by 50%, and postest by 56%. In the second trial, the motivation was 61%, the pretest was 61%, and the postest was 68%. And in the third trial, namely motivation by 80%, pretest by 77%, and postest by 85%. This study concludes that the design of the Quantum Learning learning model through the Arisan Card can improve learning motivation and student learning outcomes in the material order of the order of laws in the national legal system in Indonesia.